1989
DOI: 10.1136/jmg.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities and limitation of prenatal diagnosis and carrier determination for Duchenne and Becker muscular dystrophy using cDNA probes.

Abstract: SUMMARY Two cDNA probes, cf23a and cf56a, identify deletions of selected exons in about 50% of our DMD/BMD patients. We have estimated the most likely order of the 11 exons detectable with both probes with respect to the different extensions of the deletions. In one of our BMD pedigrees, the observed deletion could be traced in the affected males through three generations. This result shows that with the use of cDNA probes detecting deletions, the only risk of error in genomic prenatal diagnosis is the general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…(Koenig et al 1987(Koenig et al , 1989Darras et al 1988b;Wapenaar et al 1988;Baumbach et al 1989;Lindl6f et al 1989). Accurate prenatal diagnosis and carrier detection based on deletion analysis is possible by Southern blotting using eDNA or genomic probes and by PCR (Darras et al 1988a;Cole et al 1988;Speer et al 1989;Chamberlain et al 1988Chamberlain et al , 1989Chamberlain et al , 1990.…”
Section: Offprint Requests To" a E Covonementioning
confidence: 99%
“…(Koenig et al 1987(Koenig et al , 1989Darras et al 1988b;Wapenaar et al 1988;Baumbach et al 1989;Lindl6f et al 1989). Accurate prenatal diagnosis and carrier detection based on deletion analysis is possible by Southern blotting using eDNA or genomic probes and by PCR (Darras et al 1988a;Cole et al 1988;Speer et al 1989;Chamberlain et al 1988Chamberlain et al , 1989Chamberlain et al , 1990.…”
Section: Offprint Requests To" a E Covonementioning
confidence: 99%
“…On the autoradiograph obtained after the usual exposure time, the DNA sample Although the aim of this study was to detect DMD carrier females in this family, the finding reported here prompts us to emphasise two points: as cDNA probes are now often used in a large number of laboratories for DMD carrier detection,2 3 we suggest that when confronted with unusual band intensities, a karyotypic abnormality should be considered. In addition, laboratories dealing with blood samples alone need as much clinical and cytogenetic data as possible, in order to make a better molecular diagnosis.…”
mentioning
confidence: 82%
“…In the study of one such family using 2 7 probe 8, a deletion of the 1-25, 3-8, [1][2][3][4][5][6], and 3-7 kb HindIII fragments was seen in a boy with DMD. Visual inspection of the intensity of the 3 8 and 3 7 kb ( 6 bands diagnosed subjects 1, 3, and 6 as non-carrier females and subjects 2, 4, and 5 as DMD carriers (fig 4 1).…”
mentioning
confidence: 99%
“…Studies using :s. When the junction Southern blot hybridisation have shown that d as markers, five car-deletions or duplications of DNA containing cally diagnosed among one or more dystrophin exons are responsible wo families of DMD/ for approximately 70% of DMD/BMD s novel method allows cases.2'-0 Female carriers of rearranged dysre identification of car-trophin genes can be identified by quantitative *sforDMDIBMDwith-Southern blot analysis. However, because signal intensities of the hybridised bands must be measured accurately, results are occasionally ambiguous.1 [1][2][3][4][5][6][7][8][9][10][11][12][13] Junction fragments produced by gross alterations of the dystrophin gene are observed in 2 Materials and methods SUBJECTS We studied 27 unrelated Japanese male patients in 27 families and six female members of two of the families. Of the 27 patients, 19 with DMD and one with BMD carried partial deletions and the remaining seven DMD patients carried partial duplications in the dystrophin gene.…”
Section: Introductionmentioning
confidence: 99%